Understanding constituted by understandings - Johnsen Høines, Marit (NOMAD Nordic Studies in Mathematics Education, 2004)
While focusing on the function of language as a fundamental tool in the learning process, this article relates to a text-theoretical approach connected to frameworks developed by M.M. Bakhtin (1981, 1998) and J. Lotman (1988), in particular to their shared view of language as gaining meaning in relation to other languages. Learning is seen as developing text; it is seen as relational – as individual, social and genre-related. The empirical basis for this article emerges from a learning situation in which student teachers are searching for insight into concepts within the theory of functions. The article comprises different texts: the theoretical framework, the empirical text, and a child’s beadwork.